2022
DOI: 10.1111/1475-6773.14087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an electronic health record‐based mobility assessment and automated referral for inpatient physical therapy on patient outcomes: A quasi‐experimental study

Abstract: Objective To assess the effectiveness of a hospital physical therapy (PT) referral triggered by scores on a mobility assessment embedded in the electronic health record (EHR) and completed by nursing staff on hospital admission. Data Sources EHR and billing data from 12 acute care hospitals in a western Pennsylvania health system (January 2017–February 2018) and 11 acute care hospitals in a northeastern Ohio health system (August 2019–July 2021). Study Design We utilized a regression discontinuity design to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
1
1
Order By: Relevance
“…Our failure to observe a reduced probability of death with more therapy contrasts with studies by Freburger et al, 2 Chou et al, 30 and Momosaki et al 31 who reported an inverse relationship between physical therapy and death. Freburger et al observed a 14% reduction in the odds for their combined outcome of readmission or death when patients had >6 visits compared to patients with no physical therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…Our failure to observe a reduced probability of death with more therapy contrasts with studies by Freburger et al, 2 Chou et al, 30 and Momosaki et al 31 who reported an inverse relationship between physical therapy and death. Freburger et al observed a 14% reduction in the odds for their combined outcome of readmission or death when patients had >6 visits compared to patients with no physical therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…An example of this type of HPSSR is a study by Chou et al which employed a regression discontinuity design (RDD) to assess the impact of automated physical therapy referrals on rehospitalization or mortality for patients with stroke in 23 acute care hospitals in two different geographical regions. 21 Investigators employed a cut-off value/arbitrary threshold to make decisions on whether to provide a specific intervention/health service, in this case physical therapy. The RDD design allows investigators to the measure treatment effect and the impact of an intervention/health service by comparing those individuals above and below the predetermined cut-off value.…”
Section: Research Questions and Study Designsmentioning
confidence: 99%